Você está na página 1de 86

1.

2. A 4

S 4 A 5

 D n

 r s srs rsrr 12 34 r s

 D 3 D 4 Z 5 Z 9 S 3 A

[1]

L 8 M π 2π 12

3 M π L π P 5 π/3 2π/3 π 4π/3 5π/3 12

12 12 kπ/6 1 k 12

π/6 12

1, 2, 3, 4 r 2π/3 L s π M s r 1.4

r s

r s T 7 π L M π

π M 6 π T u v v u T uv e u u ue = u eu = u u T

u u 1 T

uu 1 = e = u 1 u.

u 1 u u r rr r

u, v w T u v w u vw

(uv)w = u(vw).

u, v w T T

)

P 2π/3 4π/3 L π ) 8

) srs

4 rsrr 12

34

srs

rsrr 12 34

) r 1 = rr, s 1 =

s,

(rs) 1 = s 1 r 1

(rs) 1 = srr, (sr) 1 = rrs

x, y xy

G G

i) x, y, z G

(xy)z = x(yz).

ii) e G x G

xe = x = ex.

iii) x G x

x 1 x = e = xx 1 .

0 x x R

CH 4 C 6 H 6 x y y x xy yx

A =

(u)

(u)

(u)

(u)

()

(u) (u) x = (u) y = (u) x 2 y 2 = 1

 (u ± v) = (u) (v) ± (u) (v), (u ± v) = (u) (v) ± (u) (v).

(t) = t t

(t) =

t + t

2

2

Id =

(0)

(0)

(0)

(0)

.

()

A 1 =

(u)

(u)

(u)

(u)

.

2.4

1)

e e

e ee = e

e ee = e e

 e = e 2) y, z x y = ey = e = (zx)y = e x = z(xy) = = ze = y x = z. e

)

) R +

i) x y z R +

R (x.y).z = x.(y.z)

ii) 1 R + 1x = x = x1

x R

+

x > 0 x

iii) x R +

x

R +

x 1

1 1

x x = 1 =

x x

R +

2.3) 2 × 2

(i) a

b

b

c

ac

=

b 2

A =

1

2

3 2 B =

4

5

5 D =

6

14

23

17

28

(i)

(ii) a

c

b

a

a 2

=

bc

a

A.B

A =

a b B

=

d

f

e

d

a

c

= b

= c

= d

= e

= f

= 0

C =

cd

+ bf

+ af

ae + bd

ce +

(ii)

(iii) a

c

b

d

= 0

A B

A.B C

det(A)

det(C) = det(A.B) = det(A).det(B)

=

0 det(B)

=

0

= 0

A = a

c

d b B =

e

g

f

h

C = j

l

m k (iii)

(A.B).C

D = aej + bgj

+ afl + bhl

cej + dgj + cfl + dhl

aek + bgk + afm + bhm

cek + dgk + cfm + dhm

.

A.(B.C)

F =

aej + afl + bgj + bhl

cej + cfl + dgj + dhl

aek + afm + bgk + bhm

cek + cfm + dgk + dhm

(A.B).C = D = F = A.(B.C)

a, b, c, d, e, f, g, h, j, k, l, m

I =

1

0

0

1

(iii) a = 1 b = 0 = c d = 1

A =

= 0

c

a

c

d b A 1 =

d

b

a

1

·

det(A)

A.A 1 = I = A 1 .A I

) f f

f 1

f : R 2 R 2 f (v) = λv v R 2 λ R

v

+

w u w, v R 2 f